The viewpoint of Iranian gynecologists and midwives on the expectations of pregnant women: A content analysis study - Mahboubeh Hajifoghaha; Fatemeh Nahidi; Masoumeh Simbar; Malihe Nasiri (Wolters Kluwer Medknow Publications, 2020)
Background: Prenatal care providers play an important role during pregnancy. Because healthcare providers provide comprehensive support to pregnant women, they must pay attention to pregnant women's expectations and efforts to meet their expectations. Understanding of pregnant women's expectations is associated with continuation of care and improving the health of the community. The present study is carried out to investigate the viewpoints of Iranian gynecologists and midwives on the expectations of pregnant women. Materials and Methods: This qualitative study was carried out on 10 prenatal care providers in Shiraz in 2018. Sampling method was purposive. Sampling continued until data saturation. Structured, face to face and in-depth interviews were used for data collection. Implementation and coding of interviews were performed simultaneously with data collection. The data were analyzed using conventional content analysis approach. The Lincoln and Guba criteria were used to increase the trustworthiness of the data. Results: Two main categories were emerged after analyzing of the data. The main category of "competent prenatal care providers" consisted of three subcategories: professional skills, communication skills, and individual characteristics. Another main category was the "appropriate pregnancy and childbirth centers" that included two subcategories of personnel-facilities and management system. Conclusions: According to the results, prenatal care providers have been aware that women during pregnancy period expect to have competent providers. Also, they tend that receive pregnancy care and delivery from appropriate pregnancy and childbirth centers.